Microservices for modern commerce : dramatically increase development velocity by applying microservices to commerce - Goetsch, Kelly (O'Reilly Media, 2017)
For consumers, there's no distinction between commerce and ecommerce. People shopping for products today expect to have the same experience with a brand no matter what sales channel they choose--website, mobile device, wearable, internet-enabled TV, kiosk, or retail outlet. Most retailers already rely heavily on software to drive sales, but their monolithic enterprise commerce applications are too slow to keep up with the new omnichannel commerce landscape. The solution? Microservices. This report examines how microservices not only help retailers provide a seamless shopping experience across channels, but also enable you to introduce new features to the market quickly--often within days or even hours. Author Kelly Goetsch shows you what it takes to build individual microservices, as well as the architecture necessary to connect and deploy them to your application. Amazon.com has used microservices since 2006, and today the company has thousands of individual microservices that serve as building blocks for hundreds of UIs. They can iterate on features over the course of just a few days rather than the months or even years it takes most retailers. It's a blueprint for success your company cannot ignore. With this report, you'll learn: Where microservices came from The guiding technical and non-technical principles behind microservices The inner architecture of individual microservices The outer architecture of how to connect together dozens, hundreds or even thousands of microservices How to incrementally adopt microservices Kelly Goetsch is Chief Product Officer at commercetools, overseeing product management, development, and operations. He came to commercetools from Oracle, where he led product management for its microservices initiatives. Prior to Oracle, he was a senior architect at ATG, an early pioneer in the commerce space. He is the author of eCommerce in the Cloud (O'Reilly).